What’s in, and what’s out? A study of student choice of learning activities in a flipped EFL classroom - Shen Yan (Journal of China Computer-Assisted Language Learning)
Flipping pedagogy has gained popularity in higher education. Learning activities are decisive to the effectiveness of a flipped classroom. However, research dedicated to learning activities in flipped classrooms is limited in quantity and even scarcer from learners’ perspectives. This paper explores students’ choice of learning activities in and out of a flipped EFL classroom to find more targeted measures to enhance teaching and learning practices in flipped classrooms. Student proposals (n = 30) for learning activities from 30 sophomores in an integrated English course (IEC) were used as media for data collection. The technology acceptance model (TAM) was used as the analytical framework. The findings showed that the participants proposed a conventional learning method emphasising lectures and revisions, which can result from students’ understanding of effective learning and their perceived usefulness of technology. This study concluded that successful flipped teaching entails considering student needs in the e-learning environment, quality learning activities and sufficient support for students to develop their autonomy.